Academic Detailing is a Preferred Knowledge Update Tool Among Norwegian Pharmacists to Improve Antibiotic Counseling: Results From a Quantitative Study Employing the Provider Satisfaction With Academic Detailing (PSAD) and the Detailer Assessment of Visit Effectiveness (DAVE) Tools - Yngvild Kristine Rochette Bergsholm MPharm; Harald Christian Langaas MPharm; Tonje Krogstad PhD; Lene Berge Holm PhD (SAGE Publishing, 2024)
Excessive and incorrect use of antibiotics contributes to the rise of antimicrobial resistance (AMR). Given that pharmacists act as final checkpoint before antibiotics is handled over to patients, they play a crucial role in promoting proper antibiotic use and ensuring treatment adherence. However, there is often a gap between the patients' needs and perceptions, and what the pharmacists provide. Improving pharmacists' training is essential for enhancing patient-centered care. The aim of this research was to evaluate the suitability of academic detailing (AD) for improving Norwegian pharmacists' knowledge and practice on adherence promoting counseling of antibiotic patients. Key insights from prior qualitative research regarding community pharmacists' position in promoting optimized antibiotic use were incorporated in a tailored AD program. The AD's suitability was evaluated using the validated "Provider Satisfaction with Academic Detailing" (PSAD) and "Detailer Assessment of Visit Effectiveness" (DAVE) instruments. Additionally, participants preferred knowledge updates method were assessed. Eighty-one of 86 visits completed PSAD (94% response rate). Satisfaction summary score for PSAD was 40.03 (of maximum 45) and scale summary score for DAVE 12.45 (of maximum 15). One-sample t -test (P < .001) indicated preference for AD over other knowledge update methods. This study confirmed that AD is a successful knowledge updating tool for improving adherence promoting counseling among Norwegian pharmacists. Future research should align practice change intentions with actions post-AD and evaluate patient impact.